FROM ZERO TO HERO : Kisah Inspiratif Pengentasan Kemiskinan dan Stunting di Desa Margamukti Kecamatan Sumedang Utara Kabupaten Sumedang: Penelitian - N. Siti Nur’aeni Sof (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Margamukti Village initiative in North Sumedang integrated extreme poverty alleviation and stunting reduction through livestock-based food security and circular economy programs—such as biofloc fish, chickens, rabbits, sheep, and BSF maggot farming—managed by low-income households registered in the DTKS. This approach not only improved children’s intake of animal protein and household food resilience but also established income-generating activities rooted in local wisdom. Supported by innovative utilization of Village Funds and commended by the Ministry of Finance and the Regent of Sumedang as part of the Joint Movement Against Poverty and Stunting (Geber), this community empowerment model has proven effective in lowering stunting rates and enhancing long-term local welfare.